A new magnetostratigraphic framework for the Lower Miocene (Burdigalian/Ottnangian, Karpatian) in the North Alpine Foreland Basin - Reichenbacher, B.; Krijgsman, W.; Lataster, Y.; Pippèrr, M.; Van Baak, C.; Chang, L.; Kälin, D.; Jost, J.; Doppler, G.; Jung, D.; Prieto, J.; Abdul Aziz, H.; et al. (2013)
Oligocene–Miocene chronostratigraphic correlations within the Paratethys domain are still highly controversial. This study focuses on the late Early Miocene of the Swiss and S-German Molasse Basin (Late Burdigalian, Ottnangian–Karpatian). Previous studies have published different chronologies for this time interval that is represented by the biostratigraphically well constrained Upper Marine Molasse (OMM, lower and middle Ottnangian), Upper Brackish Molasse (OBM, Grimmelfingen and Kirchberg Formations, middle and upper Ottnangian to lower Karpatian, MN 4a–MN 4b) and Upper Freshwater Molasse (OSM, Karpatian–Badenian, MN 5). Here, we suggest a new chronostratigraphic framework, based on integrated magneto-litho-biostratigraphic studies on four sections and three boreholes. Our data indicate that the OBM comprises chrons 5D.1r and 5Dn (Grimmelfingen Fm), chron 5Cr (lower Kirchberg Fm) and the oldest part of chron 5Cn.3n (upper Kirchberg Fm). The OSM begins during chron 5Cn.3n, continues through 5Cn, and includes a long reversed segment that can be correlated to chron 5Br. The OMM-OSM transition was completed at 16.0 Ma in the Swiss Molasse Basin, while the OBM-OSM changeover ended at 16.6 Ma in the S-German Molasse Basin. As the lower Kirchberg Fm represents a facies of the Ottnangian, our data suggest that the Ottnangian–Karpatian boundary in the Molasse Basin is approximately at 16.8 Ma, close to the 5Cr–5Cn.3n magnetic reversal, and thus 0.4 Myr younger than the inferred age of 17.2 Ma used in recent Paratethys time scales. Notably, this would not be problematic for the Paratethys stratigraphy, because chron 5Cr is mainly represented by a sedimentation gap in the Central Paratethys. We also realise, however, that additional data is still required to definitely solve the age debate concerning this intriguing time interval in the North Alpine Foreland Basin. We dedicate this work to our dear friend and colleague Jean-Pierre Berger (8 July 1956–18 January 2012).